Trypanosoma cruzi isolation from xenoculture after in vivo and/or in vitro xenodiagnosis executed in chagasic or co-infected with HIV patients - da Conceição Bisugo, Márcia (1998)
The aim of this study was the evaluation of the performance of xenoculture as technical procedure for isolation of T. cruzi fram intestinal contents of Triatoma infestans used in xenodiagnosis applied in 78 patients, fram different states of Brazil, all of them in chranical phase of Chagas' disease, being 32 co-infected by HIV A total of 101 xenodiagnosis were dane, "in vivo" and/ar "in vitro", with 30-40 T. infestans between third and fourth instar of development. At the end of xenodiagnosis examinations, a variable number of triatomines fram each examination were seed, individually after iodine alcohol treatment, in biphasic medium Ducrey with LIT ar BHI (with gentamicine). The cultures were examined every fifteen days until three months and, isolates preserved in liquid nitrogen. Fram 101 xenodiagnosis, 73 (72,3%) were positive to T. cruzi, corresponding to 57 out 78 (73,1 %) patients. In 51 out 57 (89,5%) patients ( 26 coinfected and 31 chranic Chagas( disease ) with positive xenodiagnosis the isolation of T. cruzi were possible by the use of xenoculture.T. cruzi isolation was obtained in 25 out 26 (96,2%) coinfected patients and 26 out 31 (83,9%) between seronegatives. Fram 461 triatomines that were infected in xenodiagnosis "in vivo" ar "in vitro" it were possible the isolation of 250 (54,2%) sampies of T. cruzi. Fram 399 bugs, negatives at xenodiagnosis, we isolated, by xenoculture 25 (6,3%) T. cruzi. Among 22 dead nirnphs, for which we can "t examine in xenodiagnosis, xenoculture viabilized isolation of 2 (9,1 %) samples of T. cruri. From no one negative xenodiagnosis it were isolated T. cruzi. We observed 5% of loss of xenocultures by fungic ar bacterial contamination. We observed, also, an apparent better adaptation of slender forrns to the culture medium. Besides to possibilite T. cruzi isolation from araund 90% of patients with positive xenodiagnosis and from mare than half of infected triatomines, the xenoculture viabilized recognition and parasite isolation fram around 13,3% (27/203) of insects that were dead ar identified as negative when examined in positive xenodiagnosis.